Penggunaan Stilling Basin Tipe Bremen Modifikasi Pada Pelimpah Bendungan Tugu Di kabupaten Trenggalek - Prasetyorini, Linda; Priyantoro, Dwi (Fakultas Teknik, Universitas Brawijaya, 2015)
Tugu Dam is designed to be built in Keser River of Trenggalek city in East Java Province. The contruction of Trenggalek Dam is planned such as flood control in Trenggalek City, in addition to water supply, irrigation, hydropower and electrical energy. The spillway of the dam is designed using side channel spillway provided by straight chute. One of the important stage in these activities is a physical hydraulic model test. The model test is to evaluate and to achieve the perfect, safe and optimum hydraulic design of the spillway that conducted in the river and swamp laboratory, Water Resources Departement. The model is using undistorted model with scale of 1 to 50. Based on the research results, it can be concluded that the hydraulic performance of the original design is good, but extremely high speed in the end of chute more than 25 m/s. In order to improve the hydraulic design, it is recommended to modify the stilling basin with Bremen Modification Type. Bremen Modfication Stilling Basin is similar with plunge pool design.Keywords : spillway, stilling basin, Bremen Modification